Preliminary Study of Metamorphic Rocks from Lan Sang National Park Indication of Ancient Tectonic Events in Western Thailand - Wonglak, Somporn; Sutthirat, Chakkaphan (Bulletin of Earth Sciences of Thailand, 2021)
Metamorphic rocks have been widely exposed in all regions of Thailand. Lan Sang Metamorphic rocks have been considered as part of Chiang Mai-Lincang belt. The Lan Sang National Park located in the west of Changwat Tak is part of the affected area from northwest-southeast striking Mae Ping fault. Local rocks along the fault zone have been strongly deformed yielding steep foliation and lineation. Gneissic rocks ranging from fine- to coarse-grained textures mainly consist of quartz, plagioclase, K-feldspar, biotite and minor of amphibole and chlorite. Calc-silicate and impure marble are partly interlayered and composed of calcite, quartz, feldspar, amphibole and garnet. These rocks should have undertaken high-grade metamorphism belonging to greenschist facies to amphibolite facies Geochemical of these rocks appear to have the evolution stages of this area probably started from granitic and sedimentary protoliths prior to regional metamorphism. Subsequently, dykes and veins cross cut into these gneissic and calc-silicate rocks. Finally, after India and Eurasia plate collision may reach the ductile-brittle stage before uplifting onto the surface.